Herpes Zoster in Patient with Hypertensive Crisis: Case Report and Literature Review - Prayogi Kramy (PT Kalbe Farma Tbk., 2019)
Herpes zoster (HZ) is a disease caused by reactivation of the varicella zoster virus (VZV) latent infection after infecting it in the form of varicella. The incidence of HZ increases with as people get older as it is associated with reduced specific immunity to VZV. A recent study showed that patients who had suffered HZ would have a greater risk of stroke and myocardial infarction than people who had never had HZ. This article presents the report a case of HZ in a 70-year-old male patient involving T10-11 dermatomes with hypertensive crisis. Herpes Zoster (HZ) merupakan penyakit yang disebabkan oleh reaktivasi infeksi laten virus varicella-zoster (VVZ) setelah sebelumnya menginfeksi dalam bentuk varicella. Insidens HZ meningkat seiring bertambahnya usia berkaitan dengan berkurangnya imunitas spesifik terhadap VVZ. Penelitian terbaru menunjukkan bahwa pasien yang pernah menderita HZ lebih berisiko terkena stroke dan infark miokardial. Artikel ini membahas kasus HZ yang melibatkan dermatom T10-11 disertai krisis hipertensi pada seorang laki-laki berusia 70 tahun.